Soldabilidad de polietileno de alta densidad usando soldadura por fricción‑agitación con una herramienta de hombro no rotacional (2016)
In this work was studied the weldability of high density polyethylene (HDPE) using friction stir welding (FSW) process, and two kind of tools, denominated conventional, and non-conventional tool, which has a non-rotating shoulder. Evaluation was performed using combination of parameters of rotation speed (vW) and welding speed (vA), which were adjusted for each type of tool. Weldability was estimated based on visual inspection, the presence of discontinuities, and tests of stereoscopy and confocal microscopy, and hardness in welded joints. Results shows that the unconventional tool obtains welded joints free of discontinuities and an excellent external appearance due to low heat input. The hardness decreased in the stirred zone compared to material base, showing different behavior on the retreating and advancing sides, depending on the process parameters.